Activation of sucrose-derived carbon spheres for high-performance supercapacitor electrodes1. Issue 12 (11th February 2015) - Mao, Lu; Zhang, Yu; Hu, Yating; Ho, Kuan Hung; Ke, Qingqing; Liu, Huajun; Hu, Zhigang; Zhao, Dan; Wang, John
<x xml:space="preserve">Abstract</x> Mesoporous carbons were prepared from carbon spheres derived from hydrothermal carbonization of sucrose, followed by KOH activation. Good electrochemical performance was achieved in both aqueous and organic electrolytes.